Finding the medicine for healthcare - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
Health care costs are escalating rapidly in countries with aging populations and is often a source of headache for policymakers. Singapore, which has one of the world’s acclaimed healthcare systems, also faces the same issues of balancing social and economic objectives in its healthcare system. A healthcare expert has now proposed a radical policy shift for the Republic to meet the medical needs of its citizens.